Fitness to Plead: The Impact of Autism Spectrum Disorder. Issue 3 (26th May 2016) - Brewer, R. J.; Davies, G. M.; Blackwood, N. J.
ABSTRACT: Purpose: This study aims to investigate the cognitive deficits associated with a diagnosis of autism spectrum disorder (ASD) and their impact upon the skills necessary for fitness to plead (FTP) to a criminal charge at trial. Methodology: A between-groups study compared the performance of a group of adult participants with a diagnosis of ASD ( N = 15) with a matched control group of adults with no diagnosis of ASD ( N = 15) on an ecologically valid 15-min filmed vignette of typical Crown Court proceedings, during which they answered questions based upon cognitive skills required for FTP. The cognitive abilities of the participants were also assessed . Findings: Participants in the ASD group scored significantly lower than the control group on the measure of FTP. Specifically, the ASD group scored lower on questions relating to the procedures and processes of the courtroom. Research Implications: Future research using a larger ASD sample and comparisons to a nonforensic ASD sample is recommended to confirm and extend these findings, and further the development of appropriate supporting measures. Practical Implications: The current finding that individuals with ASD have a poorer understanding of the courtroom process than individuals without ASD suggests the need to support and implement special measures with this client group. Originality: This article introduces a standardized measure of FTP for use with individuals with ASD, which has not previously been available.